The SAGE handbook of feminist theory - Evans, Mary 1946-; Hemmings, Clare; Henry, Marsha; Johnstone, Hazel; Madhok, Sumi; Plomien, Ania; Wearing, Sadie (SAGE Publications Inc., 2014)
At no point in recorded history has there been an absence of intense, and heated, discussion about the subject of how to conduct relations between women and men. This Handbook provides a comprehensive guide to these omnipresent issues and debates, mapping the present and future of thinking about feminist theory. The chapters gathered here present the state of the art in scholarship in the field, covering: epistemology and marginality; literary, visual and cultural representations; sexuality; macro and microeconomics of gender; conflict and peace. The most important consensus in this volume is that a central organizing tenet of feminism is its willingness to examine the ways in which gender and relations between women and men have been (and are) organized. The authors bring a shared commitment to the critical appraisal of gender relations, as well as a recognition that to think 'theoretically' is not to detach concerns from lived experience but to extend the possibilities of understanding. With this focus on theory and theorizing about the world in which we live, this Handbook asks us, across all disciplines and situations, to abandon our taken-for-granted assumptions about the world and interrogate both the origin and the implications of our ideas about gender relations and feminism.--Publisher description.